Performance evaluation on electronic control systemsfor field sprayers using programmable logic controllers - Antuniassi, Ulisses Rocha [UNESP]; Figueiredo, Z. N.; de Carvalho, WPA; Pinto, D. R. (Amer Soc Agr Engineers, 2001)
The aim of this study was to develop a laboratory method for time response evaluation on electronically controlled spray equipment using Programmable Logic Controllers (PLCs). For that purpose, a PLC controlled digital drive inverter was set up to drive an asynchronous electric motor linked to a centrifugal pump on a experimental sprayer equipped with electronic flow control. The PLC was operated via RS232 serial communication from a PC computer. A user program was written to control de motor by adjusting the following system variables, all related to the motor speed: time stopped; ramp up and ramp down times, time running at a given constant speed and ramp down time to stop the motor. This set up was used in conjunction with a data acquisition system to perform laboratory tests with an electronically controlled sprayer. Time response for pressure stabilization was measured while changing the pump speed by +/-20%. The results showed that for a 0.2 s ramp time increasing the motor speed, as an example, an AgLogix Flow Control system (Midwest Technologies Inc.) took 22 s in average to readjust the pressure. When decreasing the motor speed, this time response was down to 8 s. General results also showed that this kind of methodology could make easier the definition of standards for tests on electronically controlled application equipment.
Keywords: precision agriculture; instrumentation and control; equipment automation